2020
DOI: 10.3390/atmos11060553
|View full text |Cite
|
Sign up to set email alerts
|

Pan Evaporation Estimation in Uttarakhand and Uttar Pradesh States, India: Validity of an Integrative Data Intelligence Model

Abstract: Appropriate input selection for the estimation matrix is essential when modeling non-linear progression. In this study, the feasibility of the Gamma test (GT) was investigated to extract the optimal input combination as the primary modeling step for estimating monthly pan evaporation (EPm). A new artificial intelligent (AI) model called the co-active neuro-fuzzy inference system (CANFIS) was developed for monthly EPm estimation at Pantnagar station (located in Uttarakhand State) and Nagina station (located in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 78 publications
2
18
0
Order By: Relevance
“…Many researchers have conducted research with neural networks aimed at the estimation of Ep as a function of meteorological variables (Keskin and Terzi, 2006). Several of these researchers found better results in Ep estimation with neural network than those obtained from the Priestley-Taylor and the Penman methods (Rahimikhoob, 2009;Malik et al, 2020). Consistent with other studies, this study demonstrated that modelling of Ep is possible through the use of K-SOM technique in addition to the FAO56-PM and MLR methods.…”
Section: Discussionsupporting
confidence: 84%
“…Many researchers have conducted research with neural networks aimed at the estimation of Ep as a function of meteorological variables (Keskin and Terzi, 2006). Several of these researchers found better results in Ep estimation with neural network than those obtained from the Priestley-Taylor and the Penman methods (Rahimikhoob, 2009;Malik et al, 2020). Consistent with other studies, this study demonstrated that modelling of Ep is possible through the use of K-SOM technique in addition to the FAO56-PM and MLR methods.…”
Section: Discussionsupporting
confidence: 84%
“…Pearson's correlation coefficient: CC shows the interrelation between observed and predicted values and ranges from -1 to þ1. It can be calculated as (Malik et al 2019b(Malik et al , 2020a):…”
Section: Performance Evaluation Indicatorsmentioning
confidence: 99%
“…Predicting evaporation is an essential issue for monitoring water resources. In arid regions, evaporation prediction is vital for decision-makers because of water shortage (Malik et al, 2020a;Seifi and Riahi, 2020). Direct and indirect methods are used for predicting evaporation.…”
Section: Introductionmentioning
confidence: 99%